The allocation of resources to livestock research in Africa - Toulmin, C. (International Livestock Centre for Africa, 1984)
Examines decision making models formulated to guide the allocation of funds between alternative lines of research, issues emerging from the survey to the formation of ILCA's research policy, and various theories that account for the direction that research has taken in different contexts and reviews the past allocation of resources to livestock research in 10 African countries; includes proposal for further work.